Wacana sastera Islam di Malaysia & Indonesia - Faisal Tehrani (Penerbit Universiti Putra Malaysia, 2012)
History and criticism on Islamic literature in Malaysia and Indonesia
Includes bibliographical references (pages [173]-188) and index
Keywords: Islamic literature